THE EFFECTIVENESS OF HYPNOTHERAPY AND BACK EXERCISE ON THE SMOOTHING OF BREAST MILK PRODUCTION IN POSTPARTUM WOMEN: Efektivitas Hypnotherapy Dan Back Exercise Terhadap Kelancaran Produksi ASI Pada Ibu Postpartum - Mona Dewi Utari (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2021)
The success of exclusive breastfeeding in Indonesia is very low, namely 35%, so that it requires an active role from all levels of society (Retnani, 2016). One of the cause of decreased breastfeeding is the lack of production of the hormones oxytocin and prolactin. Hypnotherapy and back exercise can increase the production of the hormones oxytocin and prolactin. The purpose of this study was to determine the effectiveness of hypnotherapy and back exercise to smooth breastfeeding. The research method was carried out using observational method. This study uses a quasi-experiment (Quasi-Experiment) with pre and post test with Non Control Design, a research design that aims to examine the causal relationship. By comparing the two evaluation results, namely the pretest and post test. The population in this study were postpartum mothers at the hospital Pekanbaru Medical Center. The result showed the effectiveness of the implementation of hypnotherapy and back exercise on the smooth production of ASI at Post Partum at PMC Hospital. And based on the T test Independent T-test obtained pvalue = 0.04 < 0.05 with a mean value in the experimental group of 8.44. With this research, it is hoped that health workers will be able to provide breast care to every postpartum mother at PMC Hospital.